Chia (Salvia hispanica) Seed Oil Modulates the Haemato-Immunological Response, Antioxidative Status and Cytokine Gene Expression of Tropical Freshwater Teleost, Labeo rohita - Sanjay Kumar Gupta; Rajan Gupta; Akruti Gupta; Md Javed Foysal; Kishore Kumar Krishnani (Biology)
The present investigation attempts to evaluate the impact of the dietary inclusion of chia (Salvia hispanica) seed oil (CSO) on the indices of haemato-immunology, metabolic enzymes, and expression of immune-responsive cytokine genes in Labeo rohita (rohu) fingerlings. The responses were observed in a 60-day feeding trial, set up with a total of 180 rohu fingerlings (19.74 ± 0.33 g) randomly allocated to four treatment groups with three replicates each. The groups were fed with a basal diet incorporated with 0%, 1.0%, 2.0%, and 3.0% CSO, denoted as control, CSO (1), CSO (2), and CSO (3), respectively. Significant (p < 0.05) augmentation of hematological indices such as total protein and globulin levels was observed in the group fed a 1.0% CSO-supplemented diet. Serum glucose, cholesterol, triglycerides, and complement reactive protein levels declined, whereas marker anti-oxidative enzymes (SOD, CAT, and GST) and protein metabolic enzymes (ALT and AST) increased (p < 0.05) in the lowest CSO-supplemented group. A significant upregulation of inflammatory cytokine viz. IL-1β, IFN-γ, TNF-α, and TLR22 alongside downregulation of IL-10 was noted in various tissues. The results support the inclusion of 1.0% CSO as a prospective dietary vegan substitute to fish oil in rohu aquaculture.